Formulation and Evaluation of Gastroretentive Floating Pellets of Nizatidine - Patel, Dr. Keyur S. (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The aim of the study was to develop gastroretentive floating pellets containing H2 –receptor antagonist, nizatidine which is primarily absorbed from stomach and has low oral bioavailability. Materials and Methods: The gastroretentive floating pellets of nizatidine were formulated using hydroxypropyl methylcellulose (HPMC) K100M and ethyl cellulose (EC) as sustained-release polymer, and NaHCO3 as a gas-forming agent. Pellets were prepared by extrusion–spheronization technique using microcrystalline cellulose as spheronizing agent. A 32 full factorial design was applied to investigate the effect of the two independent variables, that is, concentration of HPMC K100M (X1) and concentration of EC (X2) on the dependent variables, in vitro drug release at 1 h (Y1), in vitro drug release at 4 h (Y2), in vitro drug release at 8 h (Y3), and floating lag time (Y4). Results: The optimized formulation (F0) exhibits a floating lag time of around 70 ± 2 s and in vitro drug release of 99.89% at 12 h. The in vitro release of F1-F9 batches were found in between 99.87% and 84.43% at 12 h. Floating lag time of F1-F9 batches was found to be 36 ± 1 s–84 ± 3 s. Conclusion: HPMC K100 M and EC had a significant effect on floating lag time and in vitro drug release. Scanning electron microscope photomicrograph of pellets revealed that the surface was rough and the pellets were spherical shaped in nature. The in-vitro release kinetics revealed Korsmeyer-Peppas model is followed and drug release is by anomalous diffusion.